Molecular gas properties and CO-to-H2 conversion factors in the central kiloparsec of NGC 3351 - Teng, Yu-Hsuan; Sandstrom, Karin M.; Sun, Jiayi; Leroy, Adam K.; Johnson, L. Clifton; Bolatto, Alberto D.; Kruijssen, Diederik; Schruba, Andreas; Usero, Antonio; Barnes, Ashley T.; Bigiel, Frank; Blanc, Guillermo A.; et al. (The astrophysical journal, 2022)
The CO-to-H2 conversion factor (α CO) is critical to studying molecular gas and star formation in galaxies. The value of α CO has been found to vary within and between galaxies, but the specific environmental conditions that cause these variations are not fully understood. Previous observations on kiloparsec scales revealed low values of α CO in the centers of some barred spiral galaxies, including NGC 3351. We present new Atacama Large Millimeter/submillimeter Array Band 3, 6, and 7 observations of 12CO, 13CO, and C18O lines on 100 pc scales in the inner ∼2 kpc of NGC 3351. Using multiline radiative transfer modeling and a Bayesian likelihood analysis, we infer the H2 density, kinetic temperature, CO column density per line width, and CO isotopologue abundances on a pixel-by-pixel basis. Our modeling implies the existence of a dominant gas component with a density of 2-3 × 103 cm−3 in the central ∼1 kpc and a high temperature of 30-60 K near the nucleus and near the contact points that connect to the bar-driven inflows. Assuming a CO/H2 abundance of 3 × 10−4, our analysis yields α CO ∼ 0.5-2.0 M ⊙ (K km s−1 pc2)−1 with a decreasing trend with galactocentric radius in the central ∼1 kpc. The inflows show a substantially lower α CO ≲ 0.1 M ⊙ (K km s−1 pc2)−1, likely due to lower optical depths caused by turbulence or shear in the inflows. Over the whole region, this gives an intensity-weighted α CO of ∼1.5 M ⊙ (K km s−1 pc2)−1, which is similar to previous dust-modeling-based results at kiloparsec scales. This suggests that low α CO on kiloparsec scales in the centers of some barred galaxies may be due to the contribution of low-optical-depth CO emission in bar-driven inflows.